2018
DOI: 10.1021/acs.estlett.8b00231
|View full text |Cite
|
Sign up to set email alerts
|

Photodegradation of Secondary Organic Aerosol Material Quantified with a Quartz Crystal Microbalance

Abstract: We used a quartz crystal microbalance (QCM) to quantify the mass loss resulting from exposure of secondary organic aerosol (SOA) particles deposited on the QCM crystal to 254, 305, and 365 nm radiation. We coupled the QCM setup to a proton transfer reaction time-of-flight mass spectrometer (PTR-ToF-MS) to chemically resolve the photoproduced volatile organic compounds (VOCs) responsible for the mass loss. The photoproduced VOCs detected by the PTR-ToF-MS accounted for ∼50% of the mass loss rates measured with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
45
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(56 citation statements)
references
References 45 publications
4
45
1
Order By: Relevance
“…The maximum signal of these acids is observed well after -pinene is depleted in the gas phase and with substantial delay relative to both the nitrate CIMS HOMs in the gas phase and the peak of the particle mass. Formic acid and/or other low-molecular weight carbonyls/ketones have been reported previously during photooxidation experiments of monoterpenes, where these molecules were attributed to gas-phase photooxidation reactions (44,45). A more recent study observed a similar trend for small acids and carbonyls from the ozonolysis of limonene, where this was explained by secondary OH-mediated fragmentation of the limonene backbone (33).…”
Section: Discussionsupporting
confidence: 72%
“…The maximum signal of these acids is observed well after -pinene is depleted in the gas phase and with substantial delay relative to both the nitrate CIMS HOMs in the gas phase and the peak of the particle mass. Formic acid and/or other low-molecular weight carbonyls/ketones have been reported previously during photooxidation experiments of monoterpenes, where these molecules were attributed to gas-phase photooxidation reactions (44,45). A more recent study observed a similar trend for small acids and carbonyls from the ozonolysis of limonene, where this was explained by secondary OH-mediated fragmentation of the limonene backbone (33).…”
Section: Discussionsupporting
confidence: 72%
“…It is likely that there could be compensating errors in SOA‐related to stronger photolysis and weaker wet deposition in E3SM. Laboratory measurements by Zawadowicz et al (2020) suggest that isoprene and monoterpene SOA decays at the rate of 1.5% and 0.8% of JNO 2 , respectively, which are higher than the 0.04% of JNO 2 values used in this study and previous studies (Hodzic et al, 2016; Malecha et al, 2018). However, Zawadowicz et al (2020) also reported that 10% and 30% of isoprene and monoterpene SOA, respectively, did not undergo photolytic loss, which should be taken into account in future studies.…”
Section: Results: Simulation Of Global Oa Budgets and Distributionscontrasting
confidence: 50%
“…Laboratory studies also suggest that photolysis of SOA particles can remove tropospheric aerosols on time scales comparable to those of wet scavenging, and the photolysis rate depends on SOA composition, for example, differences in photolysis rates of isoprene versus terpene precursor‐derived SOA and O/C ratios (Epstein et al, 2014; Henry & Donahue, 2012; Malecha et al, 2018; O'Brien & Kroll, 2019; Wong et al, 2014; Zawadowicz et al, 2020). Hodzic et al (2016) investigated the role of photolysis on simulated SOA loadings and lifetimes in the atmosphere using a global model (GEOS‐Chem).…”
Section: Introductionmentioning
confidence: 99%
“…24,42,49 Laboratory studies show that photo degradation could affect SOA budgets by a loss rate of at least 1% per 24 h with considerably higher rates in the stratosphere leading to the prediction that photo degradation efficiently depletes organic particles from the stratosphere. 29 Modeling indicates a tropospheric photolytic loss rate of 40-60% of SOA mass over 10 days for most species. 50 Due to the low probability of cloud formation the aerosol transport times in the stratosphere are much longer than in the troposphere.…”
Section: Discussionmentioning
confidence: 99%
“…25,26 Studies that deal with formation of organic aerosol in the stratosphere are few, although some infer stratospheric implications from laboratory studies. [27][28][29] Most of the observations of organic aerosol instead have been obtained in the troposphere or in laboratory experiments. 30,31 Primary organic aerosol (POA) and volatile organic compounds (VOC) are oxidized in the atmosphere.…”
Section: Introductionmentioning
confidence: 99%